2015
DOI: 10.5489/cuaj.2711
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of sacral neuromodulation in overactive bladder: A Canadian perspective

Abstract: Introduction: Refractory overactive bladder (OAB) with urge incontinence is an underdiagnosed condition with substantial burden on the healthcare system and diminished patient's quality-of-life. Many patients will fail conservative treatment with optimized medical-therapy (OMT) and may benefit from minimally invasive procedures, including sacral-neuromodulation (SNM) or botulinum-toxin (BonT-A). The goal of this study was to estimate the costefectiveness of SNM vs. OMT and BonT-A as important parameters from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The rechargeable Axonics r‐SNM System is designed to have a 15‐year life. This rechargeable SNM system may further enhance the cost‐superiority of SNM compared to Botox and percutaneous tibial nerve stimulation . The long‐term follow‐up of this study will provide data to assess the cost implications of the system and validate the longevity of the device as well as provide insights into patient preference for a rechargeable system.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The rechargeable Axonics r‐SNM System is designed to have a 15‐year life. This rechargeable SNM system may further enhance the cost‐superiority of SNM compared to Botox and percutaneous tibial nerve stimulation . The long‐term follow‐up of this study will provide data to assess the cost implications of the system and validate the longevity of the device as well as provide insights into patient preference for a rechargeable system.…”
Section: Discussionmentioning
confidence: 93%
“…The rechargeable SNM device, modeled with a 10‐year life, was projected to save the United States healthcare system $12 billion over a 15‐year period . Non‐rechargeable SNM therapy has been shown to be a cost‐effective long‐term treatment of OAB in Europe and Canada, including studies showing that SNM is more cost‐effective than other third line OAB therapies . The rechargeable Axonics r‐SNM System is designed to have a 15‐year life.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in the Canadian, Italian, and the UK healthcare systems, SNM was estimated to be more cost‐effective in the long term . Furthermore, the use of different models based on a great variance of clinical parameters could also contribute to the conflicting results of comparative cost‐effectiveness studies. A stark example is a study based on the Dutch healthcare system whereupon SNM was found to be more cost‐effective than Botox® after 4 years of treatment but with a model using general anesthesia for both procedures.…”
Section: Methodsmentioning
confidence: 99%
“…The implant is expensive, and the battery pack has to be replaced once it has discharged. However, if viewed in the longer term, the cost may be comparable to that of other treatments 54 . Incontinence episodes and voiding frequency are both reduced while receiving sacral nerve stimulation, and this is associated with improved quality of life 55 , 56 .…”
Section: Treatmentmentioning
confidence: 99%